1988
DOI: 10.1093/nar/16.22.10441
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, molecular characterization and chromosome localization of the inorganic pyropbosphatase (PPA) gene from S.cerevisiae

Abstract: The gene for Saccharomyces cerevisiae inorganic pyrophosphatase, PPA, has been cloned by hybridization of "long" oligonucleotide probes with both cDNA and genomic S. cerevisiae libraries. The nucleotide sequence of 1612 bp from a genomic subclone that includes the entire coding region gives a deduced amino acid sequence that has nine differences (out of a total of 286 residues) from the previously published amino acid sequence that was determined directly. The codon usage in PPA is as expected for a "highly ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 42 publications
0
44
0
Order By: Relevance
“…Tyr 139, which forms a hydrogen bond to the anion in the present structure, can serve as a proton donor for this Pi. It is difficult to be certain Amino acid sequences have been determined for soluble PPases from Saccharomyces cerevisiae (cytoplasmic, Kolakowski et al, 1988; mitochondrial, Lundin et al, IWI), Schizosaccharomyces pombe (Kawasaki et al, 1990), Kluyveromyces lactis (Stark & Milner, 1989), bovine retina (Yang & Wensel, 1992), Arabidopsk thaliana (Kieber & Signer, 1991), E. coli (Lahti et al, 1988), Thermoplasma acidophilum (Richter & Schafer, 1992), thermophilic bacterium PS-3 (Ichiba et al, 1990), Bacillusstearothermophilus and 7: thermophilus (Ishii K, Shibuya K, Kaji H, Satoh T, Teplyakov A, Obmolova G , Kuranova I, Samejima T, manuscript in prep.). Their alignment clearly shows 2 distinct groups with much higher similarity inside the groups than between them.…”
Section: Active Center and Catalytic Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Tyr 139, which forms a hydrogen bond to the anion in the present structure, can serve as a proton donor for this Pi. It is difficult to be certain Amino acid sequences have been determined for soluble PPases from Saccharomyces cerevisiae (cytoplasmic, Kolakowski et al, 1988; mitochondrial, Lundin et al, IWI), Schizosaccharomyces pombe (Kawasaki et al, 1990), Kluyveromyces lactis (Stark & Milner, 1989), bovine retina (Yang & Wensel, 1992), Arabidopsk thaliana (Kieber & Signer, 1991), E. coli (Lahti et al, 1988), Thermoplasma acidophilum (Richter & Schafer, 1992), thermophilic bacterium PS-3 (Ichiba et al, 1990), Bacillusstearothermophilus and 7: thermophilus (Ishii K, Shibuya K, Kaji H, Satoh T, Teplyakov A, Obmolova G , Kuranova I, Samejima T, manuscript in prep.). Their alignment clearly shows 2 distinct groups with much higher similarity inside the groups than between them.…”
Section: Active Center and Catalytic Mechanismmentioning
confidence: 99%
“…Extensive chemical modification studies indicated residues that might be essential for catalytic activity and substrate binding (Cooperman, 1982). The genes encoding these PPases have been cloned (Kolakowski et al, 1988;Lahti et al, 1988) and site-directed mutagenesis studies of the catalytic mechanism are now under way (Lahti et al, 1990b(Lahti et al, , 1991. Thus, detailed 3-dimensional information on PPases is urgently required.…”
mentioning
confidence: 99%
“…Their genes have been recently cloned, and experiments involving site-directed mutagenesis are now under way [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic pyrophosphatase (EC 3.6.1.1; PPase) 1 catalyzes reversible phosphoryl transfer from pyrophosphate (PP i ) to water, a metabolically important reaction chemically similar to that catalyzed by numerous ATPases and GTPases. Yeast PPase is a homodimer containing 286 amino acid residues/ monomer (1) and requiring three or four divalent metal ions for catalysis, with Mg 2ϩ conferring the highest activity (2)(3)(4)(5).…”
mentioning
confidence: 99%